Transmission of respiratory viruses when using public ground transport: A rapid review to inform public health recommendations during the COVID-19 pandemic. - Zhen J; Chan C; Schoonees A; Apatu E; Thabane L; Young T (SA MEDICAL ASSOC, 2020)
In response to the COVID-19 pandemic, numerous countries worldwide declared national states of emergency and implemented interventions to minimise the risk of transmission among the public. Evidence was needed to inform strategies for limiting COVID-19 transmission on public transport. On 20 March 2020, we searched MEDLINE, CENTRAL, Web of Science and the World Health Organization's database of 'Global research on coronavirus disease (COVID-19)' to conduct a rapid review on interventions that reduce viral transmission on public ground transport. After screening 74 records, we identified 4 eligible studies. These studies suggest an increased risk of viral transmission with public transportation use that may be reduced with improved ventilation. International and national guidelines suggest the following strategies: keep the public informed, stay at home when sick, and minimise public transport use. Where use is unavoidable, environmental control, respiratory etiquette and hand hygiene are recommended, while a risk-based approach needs to guide the use of non-medical masks.
Keywords: COVID-19; Coronavirus Infections; Hand Hygiene; Humans; Masks; Pandemics; Pneumonia, Viral; Public Health; Respiratory Tract Infections; Transportation; Ventilation